2015
DOI: 10.1007/jhep01(2015)138
|View full text |Cite
|
Sign up to set email alerts
|

The a-function for gauge theories

Abstract: Abstract:The a-function is a proposed quantity defined for quantum field theories which has a monotonic behaviour along renormalisation group flows, being related to the β-functions via a gradient flow equation involving a positive definite metric. We construct the a-function at four-loop order for a general gauge theory with fermions and scalars, using only one and two loop β-functions; we are then able to provide a stringent consistency check on the general three-loop gauge β-function. In the case of an N = … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 70 publications
4
55
0
Order By: Relevance
“…Up to two loops, it is possible to show directly that such a decomposition of W I and Q I exists, and that T IJ is indeed symmetric, but it is unclear how the program proceeds at higher loop orders. This is perhaps not surprising, as it has already been shown that the first off-diagonal contributions to T IJ in a general theory occur at three loops [6]. When deriving constraints on the β(B)-functions, imposing symmetry on T IJ would correspond to identifying the coefficients of each pair of tensors related by the interchange of open indices I and J, and setting them equal-in six-dimensional φ 3 theory at sufficiently high loop order, it has been shown that this does indeed force an additional CC, which (rather amazingly) turn out to be satisfied by the MS coefficients, and renormalizationscheme independent [21].…”
Section: Imposing Symmetry On T Ijmentioning
confidence: 76%
See 3 more Smart Citations
“…Up to two loops, it is possible to show directly that such a decomposition of W I and Q I exists, and that T IJ is indeed symmetric, but it is unclear how the program proceeds at higher loop orders. This is perhaps not surprising, as it has already been shown that the first off-diagonal contributions to T IJ in a general theory occur at three loops [6]. When deriving constraints on the β(B)-functions, imposing symmetry on T IJ would correspond to identifying the coefficients of each pair of tensors related by the interchange of open indices I and J, and setting them equal-in six-dimensional φ 3 theory at sufficiently high loop order, it has been shown that this does indeed force an additional CC, which (rather amazingly) turn out to be satisfied by the MS coefficients, and renormalizationscheme independent [21].…”
Section: Imposing Symmetry On T Ijmentioning
confidence: 76%
“…If the kinetic terms of the theory possess a global symmetry, then β I in (1.1) is replaced by a generalized function B I , which begins to differ at three loops [5], and is related to the possible existence of theories with limit cycles [20]. While the effects of this shift have been included for the simple case of six-dimensional φ 3 theory [21] and the more complicated four-dimensional scalar-fermion theory [5], equivalent analyses for general gauge theories have not yet reached the point where considering this shift is necessary [6]. All quantities in Osborn's equation are given as functions of the couplings and group structures of the theory.…”
Section: The Long Versionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ever since it has served as a fruitful laboratory for testing different techniques by rederiving the result. Examples include four-loop perturbation theory [4], the local renormalisation group (RG) [5] and employing superspace techniques assuming a gradient flow equation [6] conforming an older conjecture [7].…”
Section: Introductionmentioning
confidence: 99%